Increased Concentration of Bioethanol by Rectification Distillation Sieve Tray Type - Yuana Susmiati; Mochamad Nuruddin (UPT Penerbitan Universitas Jember, 2016)
Bioethanol is one of the alternative energy which can be used to replace fossil fuels. Bioethanol used are typically high alcohol concentration. In the process of making bioethanol is usually produced with low alcohol content, hence the need for a purification process so that the consentrations are increased. One of bioethanol purification process is rectification distillation. This study aimed to test the rectification distillation apparatus sieve tray type and verify whether the alcohol content measurement using a pycnometer according to alcoholmeter. The results showed that the apparatus can be used to increase the ethanol concentration of 38% to 53%. This research can be demonstrated that the measurement of the concentration of ethanol by pycnometer method not much different from using alcoholmeter.